IT governance enablers: a systematic literature review - Henriques, D.; Pereira, R.; Almeida, R.; Mira da Silva, M. (Foresight and STI Governance, 2020)
The pace of information technology evolution calls for governance. Control Objectives for Information and Related Technologies (COBIT) is the main framework for information technology governance (ITG) and defines the concept of IT governance enablers as a critical step for any governance decision or path. This investigation aims to clarify the enablers defined by COBIT to help organizations manage their information technology. Clarity on the meaning of enabler is still lacking in the literature. Enablers are somewhat described in COBIT leaving space for confusion and contradictions among researchers and practitioners. The research question to be answered by this investigation concerns the definition for each enabler and how it is dictated by the COBIT framework. Further this study proposes a clarification concerning the definition of ITG enablers as addressed by COBIT and several filtration stages and criteria were used to select high-quality studies. Given the aim of this research, the authors adopted a systematic literature review (SLR) methodology to analyze and synthesize the knowledge about the enablers from COBIT from the literature. Our findings may be used by future researchers to better define the scope of their definitions of enablers, to help future studies regarding the relationship of enablers with any technology or field, and to help future investigations about IT governance and its scope within an organization.